New basal hadrosauroid (Dinosauria: Ornithopoda) from the Lower Cretaceous Kitadani Formation, Fukui, central Japan - Shibata, Masateru; Azuma, Yoichi (Zootaxa, 2015)
A new basal hadrosauroid, Koshisaurus katsuyama, from the Lower Cretaceous Kitadani Formation in Fukui, central Japan, is reported. The new taxon is distinguished by an autapomorphy and a unique combination of maxillary, vertebral, pubic and femoral characters. A phylogenetic analysis indicates that Koshisaurus is positioned as a basal member of Hadrosauroidea and is more derived than the contemporaneous Fukuisaurus, which is a non-hadrosauroid hadrosauriform. The presence of the antorbital fossa on the maxilla and at least three subsidiary ridges on the labial side of maxillary tooth crown implies that Koshisaurus was among the most basal hadrosauroids. This discovery indicates a higher diversity of hadrosauroids along the eastern margin of the Asian continent in the Early Cretaceous.